Post-high school aspirations of rural Newfoundland and Labrador youth years after the cod moratorium : a new generation - Pinhorn, Lisa L., 1968- (2002)
Thesis (M.Ed.)--Memorial University of Newfoundland, 2002. Education Bibliography: leaves 144-151 Rural Newfoundland and Labrador youth who live in communities experiencing economic uncertainty could be the first generation of their families to enroll in post-secondary programs. Literature describes such "Potential First-Generation Post-Secondary Students” as less likely to aspire to post-secondary programs and gives eventual risks for attrition. Sixteen high school students from two isolated island communities of Newfoundland and Labrador were surveyed and interviewed to investigate post-high school aspirations of these youth. All participants reported wanting to attend post-secondary education and training programs and feeling that program cost was the greatest barrier to their successful completion. Recommendations are made to encourage the development of practical initiatives for student service departments in support of First-Generation Post-Secondary Students while attending programs.